A Qualitative Study of Food Choices of School Adolescents in Nepal - Ghimire, Maya Nath; Adhikari, Sarita Devi (Nepal Journal of Multidisciplinary Research, 2019)
The study was conducted in three districts: Lamjung, Chitawan and Kathmandu. All the participants were 14–19 years adolescents. The study was conducted face to face interview method. The findings show that almost adolescents’ normal ffod items for lunch and dinner are Pulse, Rice, Vegetable curry, pickle and meat (weekly or on a special day). All the young like dumplings, chowmin, tea and biscuits or cookies, egg, grams, and Haluwa (Porridge). Some adolescents from Lamjung take pop-corn and fried beans as day meal. Adolescents from Kathmandu and Chitawan mostly like junk food mainly Chatpat.